Significance of Serum Antibody Test for Toxocariasis in Healthy Healthcare Examinees with Eosinophilia in Seoul and Gyeongsangnam-do, Korea - Kim, Hong Seok (J Korean Med Sci, 2014)
There have been numerous reports on the relationship between eosinophilia and toxocariasis. The present study investigated seropositive rates of toxocariasis among healthy people with or without eosinophilia in urban and rural areas, and assessed risk factors for positive antibody test. A total of 610 healthy people, who visited health check-up (Medicheck®, Korea Association of Health Promotion), 310 from Seoul and 300 from Gyeongsangnam-do, were subjected for this study. Their serum samples were tested by ELISA with the crude antigen of Toxocara canis larvae. Cross-reactions with other tissue invading helminth antigens were also investigated. Total antibody positive rate of toxocariasis was 8.7% of the 610 subjects. When the subjects were grouped into 3 by their eosinophil counts, the antibody positive rates significantly differed by the groups; 5.9% (18/306) in the group<350/µL, 10.0% (11/110) in the group 350-500/µL, and 12.4% (24/194) in the group>500/µL (P=0.028). A total of 22 serum samples cross-reacted with other tissue-invading helminth antigens. A questionnaire analysis recognized drinking alcohol and smoking as significant risk factors of toxocariasis. In conclusion, toxocariasis antibody positive rate is correlated with eosinophil counts. It is recommended that healthy subjects with eosinophilia by routine health examination and risk factors undergo Toxocara serology by multiantigen ELISA to investigate etiology. GRAPHICAL ABSTRACT: [Image: see text]